Human Occupation of the North American Colorado Plateau ∼37,000 Years Ago - Rowe, Timothy B.; Stafford, Thomas W.; Fisher, Daniel C.; Enghild, Jan J.; Quigg, J. Michael; Ketcham, Richard A.; Sagebiel, J. Chris; Hanna, Romy; Colbert, Matthew W. (Frontiers in Ecology and Evolution, 2022)
Calibrating human population dispersals across Earth’s surface is fundamental to assessing rates and timing of anthropogenic impacts and distinguishing ecological phenomena influenced by humans from those that were not. Here, we describe the Hartley mammoth locality, which dates to 38,900-36,250 cal BP by AMS 14C measurement of hydroxyproline from bone collagen. Computed tomography (CT and µCT) and other state-of-the-art instrumentation revealed multiple lines of taphonomic evidence suggesting that two mammoths were butchered using expedient lithic and bone technology, and evidence diagnostic of controlled (domestic) fire. We accept the standard view that elaborate stone technology of the Eurasian Upper Paleolithic was introduced into the Americas by arrival of the Native American clade ~16,000 cal BP. It follows that older cultural sites in the Americas might only be diagnosed using nuanced taphonomic approaches such as those we employ. That this may be an ancient cultural site is corroborated by independent genetic evidence of two founding populations for the Americas, which raised the possibility of a migration into the Americas by people of East Asian ancestry that preceded the Native American clade by millennia. The Hartley mammoth locality provides a new deep point of chronologic reference for occupation of the Americas and the attainment by humans of a near-global distribution.